Draft Eighth Five Year Plan 1990-95 and Draft Annual Plan 1991-92 (Volume I and II) Scheme-Wise Details Volume II Union Territory of Pondicherry - Planning Commission (Planning Commission, 1990)
The massive expansion of educational facilities helped to achieve near 100% enrolment in the elementary education sector. However in the process the qualitative aspects of education need crater alterations.
Government of Pondicherry Planning and Research Department